Real-time PCR has advantages over culture-based methods in identifying major airway bacterial pathogens in chronic obstructive pulmonary disease: Results from three clinical studies in Europe and North America - Schoonbroodt, Sonia; Ichanté, Jean-Laurent; Boffé, Sophie; Devos, Nathalie; Devaster, Jeanne-Marie; Taddei, Laura; Rondini, Simona; Arora, Ashwani Kumar; Pascal, Thierry; Malvaux, Ludovic (Frontiers in Microbiology, 2023)
We compared the performance of real-time PCR with culture-based methods for identifying bacteria in sputum samples from patients with COPD in three studies. This was an exploratory analysis of sputum samples collected during an observational study of 127 patients (AERIS; NCT01360398), phase 2 study of 145 patients (NTHI-004; NCT02075541), and phase 2b study of 606 patients (NTHI-MCAT-002; NCT03281876). Bacteria were identified by culture-based microbiological methods in local laboratories using fresh samples or by real-time PCR in a central laboratory using frozen samples. Haemophilus influenzae positivity with culture was differentiated from H. haemolyticus positivity by microarray analysis or PCR. The feasibility of bacterial detection by culture-based methods on previously frozen samples was also examined in the NTHI-004 study. Bacterial detection results from both culture-based and PCR assays were available from 2293 samples from AERIS, 974 from the NTHI-004 study, and 1736 from the NTHI-MCAT-002 study. Quantitative real-time PCR (qPCR) showed higher positivity rates than culture for H. influenzae (percentages for each study: 43.4% versus 26.2%, 47.1% versus 23.6%, 32.7% versus 10.4%) and Moraxella catarrhalis (12.9% versus 6.3%, 19.0% versus 6.0%, 15.5% versus 4.1%). In the NTHI-004 and NTHI-MCAT-002 studies, positivity rates were higher with qPCR for Streptococcus pneumoniae (15.6% versus 6.1%, 15.5% versus 3.8%); in AERIS, a lower rate with qPCR than with culture (11.0% versus 17.4%) was explained by misidentification of S. pseudopneumoniae/mitis isolates via conventional microbiological methods. Concordance analysis showed lowest overall agreement for H. influenzae (82.0%, 75.6%, 77.6%), due mainly to culture-negative/qPCR-positive samples, indicating lower sensitivity of the culture-based methods. The lowest positive agreement (culture-positive/qPCR-positive samples) was observed for S. pneumoniae (35.1%, 71.2%, 71.2%). Bacterial load values for each species showed a proportion of culture-negative samples with a load detected by qPCR; for some samples, the loads were in line with those observed in culture-positive samples. In the NTHI-004 study, of fresh samples that tested culture-positive, less than 50% remained culture-positive when tested from freeze/thawed samples. In conclusion, real-time PCR on frozen sputum samples has enhanced sensitivity and specificity over culture-based methods, supporting its use for the identification of common respiratory bacterial species in patients with COPD.